Gene modification of the acetate biosynthesis pathway in Escherichia coli and implementation of the cell recycling technology to increase L-tryptophan production. - Qingyang Xu; Fang Bai; Ning Chen; Gang Bai (PLoS ONE)
The implementation of a novel cell recycling technology based on a special disk centrifuge during microbial fermentation process can continuously separate the product and harmful intermediates, while maintaining the cell viability owing to the installed cooling system. Acetate accumulation is an often encountered problem in L-tryptophan fermentation by Escherichia coli. To extend our previous studies, the current study deleted the key genes underlying acetate biosynthesis to improve l-tryptophan production. The deletion of the phosphotransacetylase (pta)-acetate kinase (ackA) pathway in a gltB (encoding glutamate synthase) mutant of E. coli TRTHB, led to the highest production of l-tryptophan (47.18 g/L) and glucose conversion rate (17.83%), with a marked reduction in acetate accumulation (1.22 g/L). This strain, TRTHBPA, was then used to investigate the effects of the cell recycling process on L-tryptophan fermentation. Four different strategies were developed concerning two issues, the volume ratio of the concentrated cell solution and clear solution and the cell recycling period. With strategy I (concentrated cell solution: clear solution, 1: 1; cell recycling within 24-30 h), L-tryptophan production and the glucose conversion rate increased to 55.12 g/L and 19.75%, respectively, 17.55% and 10.77% higher than those without the cell recycling. In addition, the biomass increased by 13.52% and the fermentation period was shortened from 40 h to 32 h. These results indicated that the cell recycling technology significantly improved L-tryptophan production by E. coli.